Implementation of Worship Diligently and Eating Breakfast Together at Elementary School - Sari, Desy Nawang; Sutarman, Sutarman; Yusutria, Yusutria; Masduki, Yusron (Early Publishing, 2025)
This study aims to analyze the implementation of the Berirama (Worship Diligently and Breakfast Together) habituation program at Kasongan State Elementary School, Bantul, Yogyakarta. This research employed a qualitative approach using a case study design. Data were collected through observation, in-depth interviews, and documentation involving the principal, teachers, students, and parents. The findings indicate that the Berirama program is implemented systematically, in a structured and sustainable manner through congregational Dhuha prayers, dhikr, Qur’an recitation, and breakfast activities conducted before the learning process begins. The program has evolved beyond a school routine into a process of character building through religious habituation and healthy lifestyle practices. Muslim students participate in congregational worship activities, while non-Muslim students receive spiritual guidance according to their beliefs. The implementation is supported by school policies, teachers’ involvement, and active parental participation. This program contributes to establishing a disciplined school culture, improving students’ learning readiness, and shaping sustainable character development through an integrated model combining spiritual, social, and health dimensions.